Evaluating planning and delivery performance of water user associations (WUAs) in Osh Province, Kyrgyzstan - Kazbekov, Jusipbek S.; Abdullaev, Iskandar; Manthrithilake, Herath; Qureshi, Asad Sarwar; Jumaboev, Kahramon (Elsevier, 2009)
The primary objective of an irrigation organization is to provide efficient and effective management of water resources to achieve enhanced agricultural production. Performance assessment studies provide a tool to evaluate and promote this objective. The study examines the existing planning procedures and assesses irrigation performance of four Water User Associations (WUAs) located in Osh Province, Kyrgyzstan. Performance was evaluated using indicators of adequacy, efficiency, ependability and equity. Indicators were calculated for each irrigation season over the period 2003 to 2007. In general, all WUAs were found to be strong in terms of adequacy and efficiency standards. However, performance with respect to dependability and equity was poor. The results suggest that more effort is needed to improve temporal uniformity and equity in water distribution. In order to achieve this, estimations of irrigation requirements by WUAmanagers needs to be improved and mechanisms eveloped to request water in quantities, which are needed to maintain equity across theWUAoutlets and among water users. The study concludes that the establishment of WUAs in Kyrgyzstan has helped to address the problem of water distribution and allocation among a large number of farmers. However, further training of farmers and managers is required to build their capacity to share water and ensure equity among users particularly during periods of less than optimal water supply. The findings of this research suggest that application of a pre-determined set of indicators can be a useful and cost effective tool to measure the performance of WUAs. This is particularly important for Central Asia where the performance of the recently established and state initiated WUAs to replace former collective farms is now a key element in future sustainable water management. The study identified uncertainties in the estimation of WUA water demands based on previousmethods and suggestsmore attention and care required in calculating water requirements.